Faktor yang Mempengaruhi Terhambatnya Usaha Mikro di Kecamatan Lenek Kabupaten Lombok Timur - Busyairi, Ahmad; Anuri, Aziz; Sulaiman, Sulaiman (ARZUSIN, 2022)
The governments programs which are principally related to developing of micro enterprise instance societies enterprise credit financing, PEN financing, and marketing aspect. However many people don’t apply the loan since they are afraid and unconfident not to be able to return it. There for it implies to the progress of their bussines. This study aims to determine the factors that influence the inhibition of the development of micro-entreprises in Lenek. This research was quantitative research and the subjects are business actors in Lenek. The results of this study based on primary data testing obtained from questionnaires and data analysis using multiple linier regression, it was showed that (1) the factors of limited capital, low quality of human resources, low market access and low partnership had a positive effect on the inhibition of micro-entreprise development in Lenek. (2) the factors of limited capital, low quality of human resources, low market access and low partnership have a positive effect with a percentage (89,5%) on the inhibition of micro-entreprise development in Lenek. (3) The factor of limited capital and low quality of human resources has the most significant influence on the inhibition of micro-entreprise development in Lenek.